The Perceptions of Stakeholders on CSR Practices in Ghana: The Case of Consumers, Employees and Managers. (Global Journal of Management and Business Research, 2024)
The literature on the perception of stakeholders on CSR has been well documented in developed countries but less is known of it in developing countries like Ghana Therefore this study investigates what stakeholders of companies know about CSR practices in Ghana and how they affect their choice and delivery of products and services Qualitative research method was used in data collection and analysis to gather rich information from customers employees and managers of six 6 companies in Ghana NVivo a qualitative data analysis computer software was used to analyze the data collected The key findings were that there are three categories of customers had knowledge in CSR employees are aware of CSR and would choose organisations that are CSR-driven managers are also aware of CSR benefits and these benefits have influence on their performance Results also revealed that there are four 4 forms of CSR practiced most in Ghana economic ethical philanthropy and environmental responsibilities respectively The study also revealed the constraints to the performance of CSR in Ghana are financial constraints and lack of vision of management team The study recommends that companies in Ghana increase their CSR activities to give rise to high profits and other benefits
Keywords: corporate social responsibility; stakeholders; customers; employees; managers